JOHNSON & KASKA 1965 FOSSIL CORALLINE ALGAE FROM GUATEMALA (REVISION OF THE JESSE HARLAN JOHNSON COLLECTION, PART 4) - Basso, Daniela; Granier, Bruno [UNESP] (Univ Studi Milano, 2018)
The original collections of eight species described by Johnson & Kaska (1965) from several Guatemalan localities and ages, have been examined, re-documented and critically revised. The generic placement of Aethesolithon guatemalaensum, Lithothamnium? primitiva, Lithothamnium diagramaticum, Lithothamnium guatemalense, Lithothamnium toltecensum, and Jania occidentalis resulted incorrect under modern taxonomic criteria, and changed accordingly, while a lectotype specimen was selected for Amphiroa guatemalense and Amphiroa kaskaella. We place tentatively L. diagramaticum in the new combination Sporolithon? diagramaticum on the base of the occurrence of secondary pit-connections and vegetative and reproductive anatomy corresponding to some extant species of the genus Sporolithon. L. toltecensum was based on few Miocene sterile thalli occurring with some fertile specimens of the same age - the latter incorrectly identified under the name L. florea brassica (Millet) Lemoine - both corresponding to the extant, long-lasting species Lithothamnion crispatum Hauck. The occurrence of large cell fusions and trichocytes, the shape and structure of the uniporate conceptacles and the dimerous construction collectively indicate that Aethesolithon guatemalaensum belongs to the genus Hydrolithon, with the new combination H. guatemalaensum (Johnson & Kaska) Basso & Granier. The vegetative anatomy of Jania occidentalis corresponds to that of a co-occurring Corallina, already identified as C. matansa Johnson. Lithothamnium? primitiva is not a coralline alga, since it is conspecific with Marinella lugeoni Pfender. The vegetative features of the sterile Lithothamnium guatemalense exclude it from the genus Lithothamnion, but the absence of important diagnostic characters suggests leaving it incertae sedis under the original binomial.
Keywords: Rhodophyta; Corallinophycidae; fossil red algae; taxonomy